TOURISM IN MALAYSIA: AN INTENSIVE STUDY OF SOCIO- ECONOMIC AND ENVIRONMENTAL IMPACTS IN TWO CENTRAL ZONES OF KLANG VALLEY - Karim, AHM Zehadul; Md. Noon, Hazizan; Mohd Noor, Noor Azlan; Mohamad Diah, Nurazzura (Research Management Centre, IIUM, 2015)
Being strategically located at the gateway of global routes with an impressive eco-environmental setting, Malaysia attracts a huge number of tourists and visitors from abroad who arrive in this country most frequently with modest expectations and aspirations. For that reason, tourism has been identified as one of the largest service-oriented industry in Malaysia, contributing to at least 10% of the country’s GDP and providing employment to millions of people. In this context, if we consider tourism positively it can be said to be a good source of income, creating job opportunities for a huge number of local people and positioning them as economically competent individuals in the community. Nevertheless, tourism may also cause a negative effect in which the local culture may be assimilated into the alien norms and behaviours through a continuous process of acculturation. It is also learned that due to day-to-day interactions with the tourists and visitors, there occurs tremendous socio-cultural impact on local values which contextually requires to be redefined. Furthermore, from the ecological perspective, tourism accelerates expansion of the urban settlement causing damages to the natural eco-system by replacing the natural habitats with pavement and unprecedented urban settlement. From this perspective, this research is designed to examine people’s perceptions and feelings about the socio-cultural and environmental impacts of tourism in Malaysia by conducting an empirical research in Klang Valley, adjoining Kuala Lumpur city.